Slavery and Unfree Labour in Nepal Documents from the 18th to Early 20th Century - Bajracharya, Manik (Documenta Nepalica - Book Series, 2022)
The topic of slavery is largely under-represented in the historiography of Nepal. This source book, aware of this disparity and wishing to encourage future studies on the topic, provides the reader with editions, translations and a study of selected documents and legal texts of Nepal from the period of the eighteenth to the early twentieth century. These sources are concerned with such different aspects of slavery as donations, transactions, bondservitude, forced labour, emancipation, and law.